Lived Islamic Environmental Ethics and Communal Ecological Transformation in An-Nur Pesantren - Muizudin; Wasil; Hassin Dzikry Ramadhan (Refleksi: Jurnal Kajian Agama dan Filsafat, 2026)
Environmental sustainability has increasingly become an important concern in Islamic studies, yet most research on eco-pesantren primarily examines environmental education or institutional waste management without explaining how Islamic environmental ethics are translated into everyday communal practice. Addressing this gap, this study investigates how Islamic environmental ethics function as a lived ethic that shapes ecological responsibility within An-Nur Pesantren, Yogyakarta. Employing a qualitative case-study approach based on interviews, participant observation, and document analysis, the research integrates Holistic Environmental Ethics with the Asset-Based Community Development (ABCD) framework to examine the relationship between religious values and ecological practices. The findings reveal that waste reduction is understood not merely as an environmental obligation but as an act of worship embedded in religious discipline and communal life. Practices such as banning single-use plastics, encouraging reusable containers, promoting modest consumption, and integrating environmental responsibility into daily pesantren routines have significantly reduced waste generation while fostering collective ecological awareness. The study argues that Islamic environmental ethics operate as a lived communal ethic capable of transforming environmental responsibility into a sustainable religious practice. It further proposes that pesantren offer a faith-based alternative to neoliberal eco-consumerism by cultivating ecological transformation through spiritual values, communal discipline, and moral formation.